Analisis Implementasi Kebijakan Pajak Hiburan Dalam Upaya Meningkatkan Pajak Daerah Pada Masa Pandemi Covid 19 Di Kota Bekasi - Mariza Putri Darliant PS; Dwikora Harjo (Jurnal Ilmu Administrasi Publik, 2022)
The phenomenon behind this research is the significant decrease in entertainment tax revenue due to the Covid-19 pandemic. The purpose of this study is to determine the implementation of the entertainment tax policy  in  an  effort  to  increase  local  tax  revenue  during  the  Covid -19 pandemic in Bekasi City, along with the obstacles and efforts made by Bapenda (Regional Revenue Agency) in increasing entertainment tax revenues during the Covid-19 pandemic in Bekasi City. This research is a descriptive  research with  a  qualitative  approach. The  method  used  is qualitative data analysis method. The results of this study indicate that the implementation of the entertainment tax policy in an effort to increase local tax revenues has been going quite well. The driving factor is that the Bekasi  City’s  Bapenda  provides  relief  in  the  administration  of  tax payments  to  taxpayers,  in  accordance  with  the  Bekasi  City  Bapenda policy regulations.